Analisis Hilangnya Pengetahuan Remaja Terhadap Budaya Madihin Suku Banjar (Studi Kasus: Kelurahan Tungkal V Kec. Seberang Kota Kab. Tanjung Jabung Barat) - Jurmia Fatma; Nurmalia Dewi; Yuslistia Opeska (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low level of knowledge among adolescents regarding madihin culture, a cultural heritage of the Banjar people in Tungkal V Village, Seberang Kota District, West Tanjung Jabung Regency, Jambi Province. Madihin is a traditional oral literary art containing poetry, rhymes, advice, and social criticism accompanied by traditional musical instruments. However, the development of modernization, the lack of cultural performances, and the lack of regeneration of traditional musicians have caused the madihin culture to be increasingly less known among the younger generation. This study aims to determine the factors causing the loss of knowledge among adolescents regarding madihin culture and the efforts that the community can take to restore this knowledge. This research uses a qualitative approach with a case study type. Data were collected through semi-structured interviews and documentation, then analyzed through data reduction, data presentation, and drawing conclusions. The results show that the low level of knowledge among adolescents is influenced by the lack of madihin performances, the minimal role of the family, the lack of government and school attention, and the influence of modernization and social media. Therefore, cooperation between the community, families, schools, and the government is needed to preserve madihin culture so that it remains known to the younger generation.